2009
DOI: 10.4070/kcj.2009.39.11.443
|View full text |Cite
|
Sign up to set email alerts
|

Cardioembolic Stroke in Atrial Fibrillation-Rationale for Preventive Closure of the Left Atrial Appendage

Abstract: Atrial fibrillation is the most common cardiac arrhythmias, and a major cause of morbidity and mortality due to cardioembolic stroke. The left atrial appendage is the major site of thrombus formation in non-valvular atrial fibrillation. Loss of atrial systole in atrial fibrillation and increased relative risk of associated stroke point strongly toward a role for stasis of blood in left atrial thrombosis, although thrombus formation is multifactorial, and much more than blood flow irregularities are implicated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 200 publications
(222 reference statements)
0
10
0
2
Order By: Relevance
“…Oral anticoagulant therapy (OAT) is the gold standard for stroke prevention in AF and reduces the stroke rate of 64% . Nevertheless, OAT in clinical practice is underused because of some caveats: increased bleeding risk (up to 4.2%/year in patient aged >75 years, need of frequent international normalized ratio [INR] checks, noncompliance of patients, interaction with other drugs and diet). Consequently 45% of AF patients with moderate to high stroke risk do not use warfarin and the percentage of OAT interruption is 38%/year .…”
Section: Introductionmentioning
confidence: 99%
“…Oral anticoagulant therapy (OAT) is the gold standard for stroke prevention in AF and reduces the stroke rate of 64% . Nevertheless, OAT in clinical practice is underused because of some caveats: increased bleeding risk (up to 4.2%/year in patient aged >75 years, need of frequent international normalized ratio [INR] checks, noncompliance of patients, interaction with other drugs and diet). Consequently 45% of AF patients with moderate to high stroke risk do not use warfarin and the percentage of OAT interruption is 38%/year .…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of AF increases with age, up to 15% in octogenerians, and continues to grow rapidly due to the increasing proportion of aging in the population. Moreover, the elderly population of today has a higher prevalence of predisposing conditions for AF, such as diabetes, heart failure, hypertension, and coronary heart disease [10]. Newly detected AF is identified in 10% of the patients who experience a stroke or a transient ischemic attack, and an additional 11% cases of AF are newly detected when patients undergo 30 days of continuous electrocardiographic monitoring [11].The left atrial appendage (LAA) is the major site of thrombus formation in non-valvular AF.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…Furthermore, one out of the bulk of unanswered questions is whether adverse hemodynamic and physiological effects may result from LAA occlusion [55]. Experimental data showed that bilateral cardiac appendectomy in dogs eliminates the release of atrial natriuretic factor and blunts renal excretion of sodium and water during acute volume load [93].…”
Section: Additional Considerations About Left Atrial Appendage Closurementioning
confidence: 99%